CSR BENEFITS AND COSTS IN A STRATEGIC APPROACH - Diana Corina Gligor – Cimpoieru (Annals of the University of Craiova: Economic Sciences Series, 2015)
In recent decades corporate social responsibility (CSR) has captured the interest of both practitioners and academics, being a concept extensively analyzed and discussed in terms of its many facets. But maybe due its complexity, still lacking a unified approach and a widely accepted definition, CSR is still often seen as having a peripheral role, auxiliary for a business organization, without even understanding its essence and having overlooked its extraordinary potential to determine multiple bivalent benefits for companies and local communities. Even if CSR benefits are identified, the analysis is often limited to an optimistic view, lacking a realistic approach that recognizes and takes into account also the costs and risks associated. With this paper we aim at identifying the most significant CSR benefits and costs in an attempt to offer a realistic pledging for the importance of CSR implementation in a strategic approach.